2013
DOI: 10.3109/01676830.2013.844173
|View full text |Cite
|
Sign up to set email alerts
|

Direct Orbital Puncture of the Cavernous Sinus for the Treatment of a Carotid-Cavernous Dural AV Fistula with a Concomitant Venous/Lymphatic Malformation

Abstract: A 37- year old male with a long history of a left orbital venous/lympathic malformation presented with ocular injection, increased proptosis and reduced left vision. Angiography demonstrated a carotid cavernous dural AV fistula combined with a concomitant venous/lymphatic malformation. After attempts at transvenous embolization, a direct uncomplicated transorbital puncture of the cavernous sinus via a lateral orbitotomy was performed with complete resolution of ocular symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…2 Coumou et al reported a case of a carotid-cavernous dural AVF concomitant with a venous/lymphatic malformation. 3 To the best of our knowledge, we describe the first case of an orbital LVM with concomitant spontaneous orbital AVF.…”
Section: Discussionmentioning
confidence: 84%
“…2 Coumou et al reported a case of a carotid-cavernous dural AVF concomitant with a venous/lymphatic malformation. 3 To the best of our knowledge, we describe the first case of an orbital LVM with concomitant spontaneous orbital AVF.…”
Section: Discussionmentioning
confidence: 84%
“…Une exophtalmie pulsatile est retrouvée dans 90% des cas, associé à une baisse de l'acuité visuelle dans 80% des cas (Mais parfois l'exophtalmie est minime et non pulsatile, difficilement trouvable à l'examen clinique) [ 3 ]. L'auscultation de la région périorbitaire et temporale retrouve un souffle intracrânien systolo-diastolique disparaissant à la compression manuelle de l'artère carotide homolatéral au niveau du cou (Cette symptomatologie peut être absente ou bien méconnue dans les grands fracas cranio-faciaux avec oedème important du visage et la FCC sera révélée plusieurs mois, voire plusieurs années après le traumatisme par des céphalées, des manifestations ophtalmologiques ou bien par une hémorragie cérébrale ou sous arachnoïdienne) [ 4 ].…”
Section: Discussionunclassified
“…L'auscultation de la région périorbitaire et temporale retrouve un souffle intracrânien systolo-diastolique disparaissant à la compression manuelle de l'artère carotide homolatéral au niveau du cou [ 4 ]. (Cette symptomatologie peut être absente ou bien méconnue dans les grands fracas cranio-faciaux avec oedème important du visage et la FCC sera révélée plusieurs mois, voire plusieurs années après le traumatisme par des céphalées, des manifestations ophtalmologiques ou bien par une hémorragie cérébrale ou sous arachnoïdienne).…”
Section: Discussionunclassified